Discovery of conjugated thiazolidinone-thiadiazole scaffold as anti-dengue virus polymerase inhibitors - TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2016)
Dengue virus (DENV) infection is a significant health threat to the global population with no therapeutic option. DENV NS5 RNA-dependent RNA polymerase (RdRp) is the key replicating protein of the virus and thus an attractive target for drug development. Herein, we report on the synthesis and biological evaluation of a series of hybrid thiazolidinone-thiadiazole derivatives as a new class of DENV-2 NS5 RdRp inhibitors. This yielded compounds 12 and 21 with IC50 values of 2.3 mu M and 2.1 mu M, respectively, as promising leads. Limited SAR analysis indicated 3-fluorobenzylidene as the optimal substituent at C5-position of the thiazolidinone core, whereas both 2-chiorophenyl and 3-fluorophenyl substituents were equally effective at C5-position of the 1,3,4-thiadiazole core. Biophysical characterization and molecular docking studies conferred the binding site of this scaffold on DENV NS5 polymerase. Binding mode of compound 21 in Thumb pocket-II of DENV-2 NS5 polymerase will form the basis for future structure-activity relationship optimization. Published by Elsevier Inc.
Keywords: Dengue virus; NS5 polymerase; RNA dependent RNA polymerase; 4-Thiazolidinones; Fluorescence quenching; 1,3,4-Thiadiazoles; RNA-SYNTHESIS; ADENOSINE NUCLEOSIDE; MYCOPHENOLIC-ACID; IN-VITRO; REPLICATION; INFECTION; ENTRY